Bowie the cultural alchemist: performing gender, synthesizing gesture and liberating identity. Issue 4 (4th July 2017) - Perrott, Lisa
Abstract: Having consistently defied the boundaries of normalized gendered behaviour, David Bowie has become synonymous with iconoclastic acts of gender transgression. His celebrity status is marked by a restless drive for re-creation, often in the form of ambiguously gendered personae. These personae do not simply originate from a need for constant transformation. Their life-span is connected with a complex process of performativity in which Bowie plays a pivotal role in re-animating the gestural traits of several other performers. Through an analysis of the videos for Boys Keep Swinging (1979) and The Stars (Are Out Tonight) (2013), this article explores Bowie's role within the cycle of performativity. Complementing this analysis, the author's interviews with New Zealand Bowie-inspired performers provide further insights about their own performativity in relation to identity.